Comparison of Del Nido Cardioplegia and Blood Cardioplegia in Terms of Development of Postoperative Atrial Fibrillation in Patients Undergoing Isolated Coronary Artery Bypass Grafting - Sanrı,Umut Serhat (2021)
Abstract Objective: Del Nido cardioplegia (DNC) has been used in pediatric cardiac surgery for many years with a single dose application and its usage in adult cardiac surgery has been increasing in recent years, with results being published. In this study, we aimed to investigate the effect of DNC on the development of postoperative atrial fibrillation (PoAF). Methods: In this retrospective observational comparative study, 255 patients who underwent isolated on-pump coronary artery bypass grafting, between January 2019 and November 2019, were enrolled. The patients were divided into two groups: DNC (n=132) and blood cardioplegia (BC) (n=123). Intraoperative and postoperative data were evaluated and compared in terms of the development of PoAF. Results: We found that the development of PoAF and the length of hospital stay remain significantly higher in the BC group (P=0.044, P<0.001, respectively). In addition, the aortic cross-clamp time and the cardioplegia volume delivered were significantly lower in the DNC group (P=0.042, P<0.001, respectively). In multivariate logistic regression analysis, only higher cardioplegia volume was determined as an independent predictor for PoAF development (OR 1.001; 95% CI 1.000-1.001; P=0.033). We did not found difference between groups in terms of troponin T, inotropic drug support, need for intraaortic balloon pump and mortality. Conclusion: This study showed that DNC can be used safely in adult coronary bypass surgery and PoAF development effect is reduced.